2021
DOI: 10.1111/jfpp.15194
|View full text |Cite
|
Sign up to set email alerts
|

β‐cyclodextrin enhanced ultrasound‐assisted extraction as a green method to recover olive pomace bioactive compounds

Abstract: Olive (Olea europaea L.) is one of the most important crops in many countries and historically played a crucial role in the human diet due to the high nutritional value of its oil (Ryan et al., 2001). The olive oil industry, seasonally and geographically concentrated, generates a considerable volume of by-products in a short period, 3-4 months a year (Aviani et al., 2009). It is estimated that 80% w/w of the processed olives are discarded as agricultural waste or by-products. There are mainly two systems of oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…The aqueous solution of the formed composite was almost transparent after 7 min US treatment both in batch (40 kHz, 450 W) and probe (26 kHz, 60 W) sonication [ 51 ]. Bioactive compounds of various physical forms of olive pomace, using βCD and US (40 kHz, 100 W), significantly increased the total phenolic content of the aqueous solution [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aqueous solution of the formed composite was almost transparent after 7 min US treatment both in batch (40 kHz, 450 W) and probe (26 kHz, 60 W) sonication [ 51 ]. Bioactive compounds of various physical forms of olive pomace, using βCD and US (40 kHz, 100 W), significantly increased the total phenolic content of the aqueous solution [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“… ------ [194] Pectin and antioxidants Carrots (Daucus carota L.) (US)-enzyme assisted extraction ES: citrate-buffer and hemicellulase or cellulase 5.00 g of sample with 500 mL of ES, sonicated (UP) at 20 kHz, 80% amplitude with with pulses (5 s on − 5 s off) for 20 min Improved the efficiency of extraction [195] Oleuropein Olive leaf UAE ES: 80% ethanol or 80% methanol 100 mg of olive lyophilized leaves,1 mL of solvent (ES), sonicated 35 °C. for 60 min ------ [196] Antioxidant Palm pressed fiber UAE ES: ethanol The UP (24 kHz 300 W.cm2) was placed at the center of the jacketed reactor containing 10 g of palm pressed fiber and 100 mL of ethanol at 20 ± 2C. Extractions were carried out for 2 h (120 W.cm2 and pulse factor of 0.4) Enhancement of the mass transfer in the system.…”
Section: Ultrasound-assisted Analytical Methodsmentioning
confidence: 99%
“…The results obtained indicated that UAE and HHPE reduced the operational time and also enhanced the extraction yield. Besides, researchers from several universities of Argentina developed analytical methods for the extraction of antioxidant compounds from plants or fruits, such as rosemary [192] , Schinus areira leaves [193] , thyme [194] , blackcurrant, raspberry and elderberry [166] , carrots [195] , and olive pomace [196] . It is important to highlight that the research developed by Maraulo et al [196] reported that during the cavitation process the particle size decreases, improving the penetration of the solvent into the vegetable tissue, and therefore improving the extraction.…”
Section: Ultrasound-assisted Analytical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…E por fim, ao que diz respeito as técnicas empregadas para os subprodutos, uma tendência atual muito expressiva é em relação a demanda por técnicas analíticas ambientalmente corretas, como a Espectroscopia Infravermelha, livre de reagentes, consequentemente não gerando efluentes (Páscoa et al, 2021). Também o método de extração por ultrassom assistida pode ser vista como uma opção ecológica (Maraulo, et al, 2021), o uso da água quente como solvente para recuperação de fenóis de folhas de oliva foi usado em detrimento aos solventes orgânicos (Monteleone et al, 2021). Assim, tecnologias verdes são incentivadas para extração de compostos e maior aplicação industrial de pigmentos naturais (Sharma, et al, 2022).…”
Section: Journal Of Theunclassified